Cadonilimab combined with trastuzumab and chemotherapy for HER2-positive gastric cancer with bone marrow metastasis and DIC: a case report and literature review - Chen, Meijing; Fan, Jiwen; Zhou, Danyang; Cheng, Boran; Wang, Shubin; Tong, Gangling (Frontiers in Immunology, 2025)
BackgroundGastric cancer (GC) is one of the most common malignancies worldwide. While bone marrow metastasis (BMM) in GC is extremely rare and often complicated by disseminated intravascular coagulation (DIC), a critical condition with a median survival of less than three months in untreated patients. Human epidermal growth factor receptor-2 (HER-2) plays a critical role in GC pathogenesis, and trastuzumab-based regimens have significantly improved outcomes in HER-2 positive metastatic GC. However, the efficacy of immune checkpoint inhibitors (ICIs) in HER-2 positive GC patients with BMM and DIC, particularly those with programmed death-ligand 1 (PD-L1) combined positive score (CPS) <1, remains unclear. Here, we present a case of GC with BMM and DIC that achieved long-term survival through treatment with cadonilimab (an anti-PD-1/CTLA-4 bispecific antibody) in combination with trastuzumab and chemotherapy. Through this case and literature review, we aim to explore optimal treatment strategies for this rare and challenging subgroup.Case presentationA 35-year-old woman presented with left hip pain. Imaging and lab tests indicated bone metastasis and DIC. Further evaluation with PET/CT, gastroscopy, and biopsy confirmed poorly differentiated gastric adenocarcinoma with bone marrow involvement (cT3N+M1, stage IVB). Immunohistochemistry demonstrated PD-L1 CPS <1 and HER-2 (2+), though fluorescence in situ hybridization (FISH) was negative. Notably, next-generation sequencing (NGS) detected a high plasma HER-2 copy number (34.88). Given her ECOG performance status of 2, initial therapy consisted of trastuzumab combined with docetaxel and fluorouracil, alongside supportive care. Within two weeks, DIC resolved, and pain significantly improved. Treatment was then escalated to a combination of cadonilimab, trastuzumab, and FLOT (5-FU, leucovorin, oxaliplatin, docetaxel). After achieving a partial response, she developed an oxaliplatin allergy, prompting a switch to maintenance therapy with cadonilimab, trastuzumab, and S-1. She achieved progression-free survival (PFS) of nearly 12 months and overall survival (OS) of approximately 15 months, with sustained quality of life throughout treatment course.ConclusionThis case demonstrates that intensive anti-tumor therapy combining HER-2-targeted agents, ICIs, and chemotherapy, alongside supportive care, can prolong survival and improve life quality in GC patients with BMM and DIC. Hematologic toxicities were the main adverse events but were tolerable, supporting the regimen’s feasibility and safety.